Investigation of the effcets of prostaglandin f2α, furosenıid and indomethacin on testosterone levels in rams - İbrahim Pirinçci; İzzet Karahan; Ferit Gürsu; Tanzer Bozkurt; Osman Güler (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the changes occurring in the levels o! serum testosterone in the rams given PGF2u. lurosemid, indomethacin and the combination of this drugs. In the study, 70 Akkaraman rams, approximately 2 years Old were used. PGFa< (0.1, 0.2 and 0.3 mg/kg), furosemid (2.0, 4.0 and 6.0 mg/kg), indomethacin (3.0, 6,0 and 9,0 mg/kg) and the combinations of these drugs were intramuscularly given the animals in one dose and in doses lollowmg on each other's (our days. The bfood samples were collected after drug administrations, Testosterone levels were determined by enzyme immunoassay analyser. The mean testosterone levels in the serum were determined to decrease 641, 528, 382 ng/dl and 507, 343. 317 ng/dl in the rams given in one dose and in doses following on each other's four days PGF2a, according to doses, respectively. On the other hand, it was established to reduce in the mean serum testosterone levels that furosemid also was given in one dose and in doses following on each other's (our days in rams. However, the mean testosterone levels in the serum were determined to increase 926, 953, 993 ng/dl and 950, 1019, 1240 ng/dl in the rams given in one dose and in doses following on each other's four days indomelhacin, respectively. In conclusion. PGF2« and furosemid were defined to decrease the levels of serum testosterone in the rams, depend on lime and doses. In contrast, indomethacin was established to increase the levels of serum testosterone in the rams.